Association Between Wait Time of Central Venous Pressure Measurement and Outcomes in Critical Patients With Acute Kidney Injury: A Retrospective Cohort Study - Yang, Qilin; Chen, Weixiao; Wen, Yichao; Zheng, Jiezhao; Chen, Jieru; Yu, Shuilian; Chen, Xiaohua; Chen, Weiyan; Xiong, Xuming; Wen, Deliang; Zhang, Zhenhui (Frontiers in Public Health, 2022)
Background: Hemodynamic management is of paramount importance in patients with acute kidney injury (AKI). Central venous pressure (CVP) has been used to assess volume status. We intended to identify the optimal time window in which to obtain CVP to avoid the incidence of adverse outcomes in patients with AKI. Methods: The study was based on the Medical Information Mart for Intensive Care (MIMIC) IV database. The primary outcome was in-hospital mortality. Secondary outcomes included the number of ICU-free day and norepinephrine -free days at 28 days after ICU admission, total fluid input and fluid balance during the first and second day. A time-dose-response relationship between wait time of CVP measurement and in-hospital mortality was implemented to find an inflection point for grouping, followed by propensity-score matching (PSM) was used to compare the outcomes between two groups. Results: 29,336 patients with AKI were enrolled, the risk of in-hospital mortality increased when the CVP acquisition times greater than 9 hours in Cox proportional hazards regression model. Compared with 8,071 patients (27.5%) who underwent CVP measurement within 9h and assigned to the early group, 21,265 patients (72.5%) who delay or not monitored CVP had a significant higher in-hospital mortality in univariate, multivariate Cox regression analyses. After adjust potential confounders by PSM, adjusted for propensity score, pairwise algorithmic, overlap weight and doubly robust analysis, the results were still stable. The HRs were 0.58-0.72, all p<0.001. E-value analysis suggested robustness to unmeasured confounding. Conclusions: Among adults with AKI in ICU, increased CVP wait time was associated with a greater risk of in-hospital mortality. In addition, early CVP monitoring perhaps contributed to shortening length of ICU stays and days of norepinephrine use, as well as better fluid management.